Design and performance evaluation of a real-time heart rate and vibration monitoring system with arduino - Al Munawir; Zakaria Husen; Zuchra Ulfa (Politeknik Negeri Lhokseumawe, 2025)
The advancement of technology in the fields of healthcare and engineering has driven the demand for portable, energy-efficient, and user-friendly physiological and mechanical monitoring devices. Heart rate (BPM) is vital in the medical field, while vibration frequency is crucial in mechanical engineering for monitoring system stability. This study designs a Beats Per Minute (BPM) and vibration frequency monitoring device based on Arduino and ESP32. The system utilizes a Pulse Sensor for BPM and an MPU6050 sensor for vibration, with real-time data displayed on the Serial Monitor and an OLED screen. The method used is a quantitative experiment involving the design, assembly, programming, and testing of the device. BPM testing was conducted on three subjects with varying activity levels, while vibration testing was performed using different voltage levels on a vibration motor. The results show high BPM accuracy, with a maximum deviation of 2.7% compared to manual methods. Vibration measurements demonstrated signal stability with less than 10% error relative to the theoretical frequency. The compact, affordable, and user-friendly design makes this tool a practical solution for health monitoring in remote areas and as a project-based educational medium. The system is feasible for further development in portable medical and engineering applications.